Wolf movement patterns and the distribution of moose kills : implications for human harvest? - Hedlund, Anders E. (SLU/Dept. of Ecology, 2010)
Most studies regarding wolf (Canis lupus) predation on moose (Alces alces) have focused on the total annual consumption of moose within a wolf territory but few have tried to describe the spatial impact of wolf predation on a local scale. In this study I have analyzed wolf movement data, wolf predation, moose hunting statistics and moose hunter observations to investigate how wolf predation affects the human harvest of moose in Scandinavia. Since wolves prey on mostly juvenile moose during summer, analysis of their summer movement patterns is crucial to understand its impact on the human harvest later during autumn. In this study both reproducing (n = 45) and non-reproducing wolves (n = 12) reduced their movement range during summer to 66% and 67% of their annual movement range, respectively. Reproducing wolves increased their movement range from early to late summer while non reproducing wolves did not. There where also a difference regarding the average distance between each moose carcass and the calculated centre of mass for all kills found during each summer study. Non reproducing wolves had an average kill distribution of 14510 m (± 7111, n = 45) while reproducing wolves had a much more restricted kill distribution of 7923 m (± 4809, n = 96). Wolf presence within moose hunting license areas during summer where negatively correlated to the distance between the area and the wolf den. Either wolf presence within the moose hunting license areas during summer or the distance between the license areas and the wolf dens where correlated to the human hunting success during autumn, with one exception. The total human hunting success where reduced in license areas where wolves had spent more time during summer. The number of cows followed by twin calves observed by hunters was the only observation variable that where significantly negatively correlated with the distance to the wolf den. These results show that pup-rearing and denning behavior has an impact on the wolves hunting behavior during summer. It also shows that this central place foraging behavior during the reproductive season influences the local human hunting success only at a small scale. The human outtake of the moose population within the wolf territories was 3.8 ± 1.6 moose per 1000 hectares. In areas where moose densities are lower wolf predation may affect the local human harvest more negatively. The long term impact of wolf predation on the local scale may be higher if wolves choose to locate their den in the same area year after year.